2007
DOI: 10.1098/rsif.2007.0212
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent spectral analysis of epidemiological time-series with wavelets

Abstract: In the current context of global infectious disease risks, a better understanding of the dynamics of major epidemics is urgently needed. Time-series analysis has appeared as an interesting approach to explore the dynamics of numerous diseases. Classical time-series methods can only be used for stationary time-series (in which the statistical properties do not vary with time). However, epidemiological time-series are typically noisy, complex and strongly non-stationary. Given this specific nature, wavelet analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
316
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(325 citation statements)
references
References 54 publications
0
316
0
9
Order By: Relevance
“…Time-series analysis of cholera cases in endemic regions such as Bangladesh shows a time variability with subannual, annual and interannual components. The low-frequency variability has been linked to long-term climatic oscillations (Pascual et al 2000;Koelle et al 2005;Cazelles et al 2007), and the overall seasonality has been found to experience competing effects with two routes of transmissions: one enhanced by increasing rainfall and the other buffered by increasing water pools (Ruiz-Moreno et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Time-series analysis of cholera cases in endemic regions such as Bangladesh shows a time variability with subannual, annual and interannual components. The low-frequency variability has been linked to long-term climatic oscillations (Pascual et al 2000;Koelle et al 2005;Cazelles et al 2007), and the overall seasonality has been found to experience competing effects with two routes of transmissions: one enhanced by increasing rainfall and the other buffered by increasing water pools (Ruiz-Moreno et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cross comparison of two different time series in time and frequency, can be done through cross wavelet and wavelet coherence analysis. Here we give a brief overview of the wavelet analysis for epidemiological time series closely following [8] and our analysis for Dengue time series.…”
Section: Compartmental Model and Reproduction Numbermentioning
confidence: 99%
“…A closer examination of these relationships needs Wavelet Coherence, discussed in next section. The wavelet coherence C x,y (a, τ ) is the cross-spectrum smoothened over time and scale (expectation value) and normalized by the smoothened spectrum of each time series [34,8]. It allows to explain the causality and coherence between the signals.…”
Section: Compartmental Model and Reproduction Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 displays the normalized NYC measles time series again, but in two different ways that highlight the changes in frequency structure that we seek to understand. The top panel of figure 5 shows weekly normalized measles on a square root scale, suppressing [36][37][38][39][40], which reveals the dominant frequencies at each point in time.…”
Section: Transition Analysismentioning
confidence: 99%